Polar seaways? maritime transport in the Arctic : an analysis of shipowners' intentions II - Huang, Linyan; Beveridge, Leah; Lasserre, Frédéric; Fournier, Melanie; Têtu, Pierre-Louis (Journal of Transport Geography, 2016)
Climate change in the Arctic is leading to the fast recession of the sea ice extent in the summer. This evolution leads several observers, scientists, media and government officials, to consider the possibility of developing new shipping routes along Arctic routes, as these routes are much shorter between Europe and Asia. The literature displays a strong interest for these potential shipping routes while the media often assume shipping companies nurture a sustained attraction for Arctic routes. This paper tackles with this idea and examines to what extent shipping companies, the ultimate economic agents, are really interested in Arctic shipping routes. The image the research portrayed is that only a minority of shipping companies are indeed interested, and those that are interested stress the destinational dimension of Arctic shipping, not transit shipping